2021
DOI: 10.3390/microorganisms9081722
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Biostimulation, Bioaugmentation and Sorption-Biological Treatment of Soil Contaminated with Petroleum Products in the Russian Subarctic

Abstract: The effectiveness of different bioremediation methods (biostimulation, bioaugmentation, the sorption-biological method) for the restoration of soil contaminated with petroleum products in the Russian Subarctic has been studied. The object of the study includes soil contaminated for 20 years with petroleum products. By laboratory experiment, we established five types of microfungi that most intensively decompose petroleum hydrocarbons: Penicillium canescens st. 1, Penicillium simplicissimum st. 1, Penicillum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The data obtained indicate that the studied strains can be recommended for the application in biotechnologies for oil removal at low temperature. It is widely believed that bioaugmentation of oil-contaminated soils by hydrocarbon-oxidizing associations in combination with biostimulation (the introduction of mineral fertilizers) gives the same results of oil degradation as the use of biostimulation of autochthonous hydrocarbon-oxidizing soil microbiota by applying mineral fertilizers, and only slightly accelerates this process [ 8 , 91 , 92 ]. However, in some cases, hydrocarbons of different classes are extracted from sediments or soil contaminated with petroleum products, and the resulting solutions are treated ex situ in bioreactors with immobilized cells [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data obtained indicate that the studied strains can be recommended for the application in biotechnologies for oil removal at low temperature. It is widely believed that bioaugmentation of oil-contaminated soils by hydrocarbon-oxidizing associations in combination with biostimulation (the introduction of mineral fertilizers) gives the same results of oil degradation as the use of biostimulation of autochthonous hydrocarbon-oxidizing soil microbiota by applying mineral fertilizers, and only slightly accelerates this process [ 8 , 91 , 92 ]. However, in some cases, hydrocarbons of different classes are extracted from sediments or soil contaminated with petroleum products, and the resulting solutions are treated ex situ in bioreactors with immobilized cells [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…The argument in favor of the use of biostimulation is that natural microorganisms are initially well adapted to the conditions of their environment. However, under Arctic conditions, the application of bioremediation methods faces additional difficulties [ 4 , 7 , 8 ]. Microorganisms living in high-latitude Arctic and Antarctic regions, along with low temperatures, can simultaneously experience several stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 5 shows three (3) common and most widely available approaches of fungal bioremediation of petro-hydrocarbons, these approaches were recently reviewed [1,26,27]. The approaches include : bioaugmentation, biostimulation, and bioaugmentationbiostimulation [17].…”
Section: Current Approaches In Fungal Bioremediation Of Petrohydrocar...mentioning
confidence: 99%
“…They found out that the addition of nutrients and biosurfactant + nutrients led to the highest biodegradation, so that 90.4 and 78 percent of oils and greases, 96.82 and 98.35 percent of aliphatic hydrocarbons and 83.58 and 72.3 percent of polyaromatic compounds were eliminated by the addition of nutrients and biosurfactant + nutrients, respectively. Myazin et al (2021) investigated the effect of adding NPK, two types of active carbon (1300 g/m2 (AC1) and 3900 g/m2 (AC2)), peat and petroleum degrading microorganisms to a soil contaminated with petroleum for 20 years. These researchers concluded that the highest hydrocarbon degradation constant (k = 0.00235) was observed in peat treatments, followed by AC1 and AC2 treatments with 0.00168 and 0.00151, respectively.…”
Section: Tph Biodegradation Percentagementioning
confidence: 99%
“…Therefore, protection of indigenous degrading microorganisms and improving the bioavailability of pollutants is also essential. Application of sorbents accelerates the bioremediation process, since sorbents act as a source of nitrogen and phosphorous for the degrading microorganisms and improve the soil moisture retention capacity and aeration (Myazin et al 2021). Active carbon as an in situ technology may be effective in bioremediation of petroleum-polluted soils because they: (1) adsorb heavy metals and toxic compounds present in polluted soils and prevent contact direct of these compounds with the degrading microorganism and other soil biota; (2) act as a carrier and a place of localization for microorganisms, stimulating their growth; (3) improve soil conditions by adsorption and retention of nutrients and increase the moisture capacity and aeration of soil (Myazin et al 2021;Agarry et al 2015).…”
Section: Applicability and Limitationsmentioning
confidence: 99%